Long-Term Efficacy and Safety of Deutetrabenazine for Chorea in Huntington's Disease: Results From the ARC-HD Open-label Study. (April 2021) - Frank, Samuel; Testa, Claudia M.; Stamler, David; Kayson, Elise; Oakes, David; Vaughan, Christina; Goldstein, Jody; Whaley, Jacquelyn; Davis, Mat D.; Gordon, Mark Forrest; Savola, Juha-Matti; ,
Abstract: Background: Chorea is a prominent motor dysfunction in Huntington's disease (HD). Deutetrabenazine, a vesicular monoamine transporter 2 (VMAT2) inhibitor, is FDA-approved for the treatment of chorea in HD. In the pivotal, 12-week First-HD trial, deutetrabenazine treatment reduced the Unified Huntington's Disease Rating Scale (UHDRS) total maximal chorea (TMC) score versus placebo. ARC-HD, an open-label extension study, evaluated long-term safety and efficacy of deutetrabenazine dosed in a response-driven manner for treatment of HD chorea. Methods: Patients who completed First-HD (Rollover) and patients who converted overnight from a stable dose of tetrabenazine (Switch) were included. Safety was assessed over the entire treatment period; exposure-adjusted incidence rates (EAIRs; adverse events [AEs] per person-year) were calculated. A stable, post-titration time point of 8 weeks was chosen for efficacy analyses. Results: Of 119 patients enrolled (Rollover, n=82; Switch, n=37), 100 (84%) completed ≥1 year of treatment (mean [SD] follow-up, 119 [48] weeks). End of study EAIRs for patients in the Rollover and Switch cohorts, respectively, were: any AE, 2.6 and 4.3; serious AEs, 0.13 and 0.14; AEs leading to dose suspension, 0.05 and 0.04. Overall, 68% and 73% of patients in Rollover and Switch, respectively, experienced a study drug–related AE. Most common AEs possibly related to study drug were somnolence (17% Rollover; 27% Switch), depression (23%; 19%), anxiety (9%; 11%), insomnia (10%; 8%), and akathisia (9%; 14%). Rates of AEs of interest include suicidality (9%; 3%) and parkinsonism (6%; 11%). In both cohorts, mean UHDRS TMC score and total motor score (TMS) decreased from baseline to Week 8; mean (SD) change in TMC score (units) was –4.4 (3.1) and –2.1 (3.3) and change in TMS was –7.1 (7.3) and –2.4 (8.7) in Rollover and Switch, respectively. While receiving stable dosing from Week 8 to 132 (or end of treatment), patients showed minimal change in TMC score (0.9 [5.0]), but TMS increased compared to Week 8 (9.0 [11.3]). Upon drug withdrawal, there were no remarkable AEs and TMC scores increased 4.4 (3.7) units compared to end of treatment. Conclusions: The type and severity of AEs observed in long-term deutetrabenazine exposure are consistent with the previous study. Efficacy in reducing chorea persisted over time. There was no unexpected worsening of HD or chorea associated with HD upon deutetrabenazine withdrawal. Funding: Teva Pharmaceutical Industries Ltd., Petach Tikva, Israel